Relationships Among Role Accuracy, Compliance, Performance Evaluation, and Satisfaction Within Managerial Dyads: Comment - Bowen, Donald D.; Byrne, Robert F. (Academy of Management Journal, 1973)
The article presents comments on the article ?Relationships Among Role Accuracy, Compliance, Performance Evaluation, and Satisfaction Within Managerial Dyads,? by C. N. Greene, published in the June 1972 issue. The author asserts that Greene's interpretation of the correlation of the perception by a manager of his supervisor's expectations for the manager's job performance comes into question after a reexamination of the original study. The author calls for further scrutiny toward Greene's data in order to procure a more accurate interpretation of the correlation between role expectation and job performance.